The circulating non-coding RNA landscape for biomarker research: lessons and prospects from cardiovascular diseases - STĘPIEŃ Ewa; COSTA Marina C; KURC Szczepan; DROŻDŻ Anna; CORTEZ-DIAS Nuno; ENGUITA Francisco J (Acta Pharmacologica Sinica, 2018)
Pervasive transcription of the human genome is responsible for the production of a myriad of non-coding RNA molecules (ncRNAs) some of them with regulatory functions. The pivotal role of ncRNAs in cardiovascular biology has been unveiled in the last decade, starting from the characterization of the involvement of micro-RNAs in cardiovascular development and function, and followed by the use of circulating ncRNAs as biomarkers of cardiovascular diseases. The human non-coding secretome is composed by several RNA species that circulate in body fluids and could be used as biomarkers for diagnosis and outcome prediction. In cardiovascular diseases, secreted ncRNAs have been described as biomarkers of several conditions including myocardial infarction, cardiac failure, and atrial fibrillation. Among circulating ncRNAs, micro-RNAs (miRNAs), long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs) have been proposed as biomarkers in different cardiovascular diseases. In comparison with standard biomarkers, the biochemical nature of ncRNAs offers better stability and flexible storage conditions of the samples, and increased sensitivity and specificity. In this review we describe the current trends and future prospects of the use of the ncRNA secretome components as biomarkers of cardiovascular diseases, including the opening questions related with their secretion mechanisms and regulatory actions.